Future prospects for cassava root yield in sub Saharan Africa - Nweke, F.; Spencer, D. (SAGE Publications, 1995)
Primary data collected over a wide area in Africa show that average cassava root yield is not declining as the population increases because the land is being cultivated more intensively in response to demographic pressures. Although fallow periods are becoming shorter, organic manuring, improved market infrastructures and the use of purchased inputs such as labour compensate for this. The yields of improved cassava varieties in Nigeria show that technology can be relied upon to raise production in future, provided that the conditions necessary for the widespread adoption of improved varieties prevail in most African countries.